Telepractice for Pediatric Dysphagia: A Case Study - Georgia A. Malandraki; Melissa Roth; Justine Joan Sheppard (International Journal of Telerehabilitation)
A closed-ended intensive pediatric swallowing telepractice program was developed and piloted in one pediatric patient with Opitz BBB/G and Asperger’s Syndromes, oropharyngeal dysphagia and aerophagia. The present study is a case report. Outcome variables included behavioral, swallowing and quality of life variables, and were assessed at baseline and at the end of the four-week program. Selective variables were also assessed at a follow-up family interview four weeks post program completion. Over the four-week intervention period, the patient demonstrated substantial improvements in: oral acceptance of eating-related objects and a variety of foods (behavioral variable), timing of voluntary saliva swallows and aerophagia levels (swallowing variables) and quality of life. Follow-up interview analysis showed that most skills were retained or improved one-month post intervention. This intensive telepractice program proved to be feasible and effective for this pediatric patient with dysphagia.